Botanical knowledge and its differentiation by age, gender and ethnicity in southwestern Niger - Ayantunde, Augustine A.; Briejer, M.; Hiernaux, Pierre H.Y.; Udo, H.M.J.; Tabo, Ramadjita (Springer, 2008)
Indigenous knowledge is unevenly distributed. Individual knowledge level may be affected by many factors such as gender, age, ethnicity, profession, religious and cultural beliefs, abundance and usefulness of the species. This study documents indigenous knowledge of herbaceous and woody plant species of farmers and herders in southwestern Niger. Specifically, we examine the effects of age, gender, and ethnicity on knowledge of local vegetation. Results from the study showed that on average a higher proportion of woody species was identified by the respondents compared to herbaceous species. Both gender and ethnicity had a significant effect on the identification of herbaceous species but no effect on identification of woody species. Respondents in lower age group (10 to 30 years) identified lower number of species compared to other age classes. There seems to be a curvilinear relationship between age of respondents and number of plant species identified. Results from this study reaffirm the uneven distribution of indigenous knowledge within a given area due to social factors. The main challenge is how to incorporate these social differences in knowledge of native plant species into sustainable management and conservation of community natural resources.